Gambaran Pengelolaan Limbah Padat Bahan Berbahaya dan Beracun (B3) Fasilitas Pelayanan Puskesmas di Kota Bandar Lampung - Pratama, Sinta Debi; Budiati, Endang; Putri, Dian Utama Pratiwi (Poltekkes Kemenkes Tanjung Karang, 2023)
Hazardous and Toxic Material Waste is the residue of a business and service facility activity containing B3. Hazardous and toxic waste (B3) at the Puskesmas has excellent potential to pollute the environment, cause accidents, and endanger public health due to viruses and bacteria that are the source of disease transmission; for this reason, this research is essential to do as an illustration of B3 waste management which has not been optimal at Health Centre in Bandar Lampung which has never been done before. The results of the research on the B3 solid waste management process at the Bandar Lampung City Health Center facilities with the same standards did not meet the technical requirements and the utilization of the facilities; the process of transporting Puskesmas waste was transported entirely to RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung City. A destruction company with a B3 waste processing operational legality permit carries out the processing, burial, and stockpiling operations. Recommendations are needed to provide policies for the Forestry Environment Service and Bandar Lampung City Health Office related to solid medical waste management with the fulfillment of waste management facilities/infrastructure and the completion of an incinerator with permission from PT. Wastec International, PT. Tenang Jaya Sejahtera, and PT. Pengolahan Limbah Industri Bekasi . In addition, it is necessary to supervise and monitor the processing of Puskesmas waste in the destruction company.